2021
DOI: 10.1007/s11069-021-04954-9
|View full text |Cite
|
Sign up to set email alerts
|

Rockfall susceptibility and runout in the Valley of the Kings

Abstract: The UNESCO world heritage site Valley of the Kings or Wadi el-Moluk (وادي الملوك) near Luxor, Egypt, hosts unique burial places of Egyptian kings and royals from the New Kingdom (c. 1539–1075 BCE) and attracts about 0.5 to 2 million tourists per year. Very steep to subvertical cliffs of Thebes Limestone surround the Valley of the Kings. The rock mass is cut by frequent joints and faults making the cliff walls prone to rockfalls. However, only few rockfall debris are found in the valley, likely due to natural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…The KV is surrounded by steep cliffs of up to 30 m in height (Figure 2b) and small hills with gentle slopes. Other important features were described by Lukovic et al [14] and include low slope angles from the crest of cliffs to the upper plateau, overhanging blocks in cliff walls, gullies crossing the valley, and branching channels used as tourist paths dipping towards the north (<10 • ). Lukovic et al [14] also reported bedding angles from subhorizontal (15 • ) for unfaulted sections to steep angles (30 • ) for those affected by listric faults.…”
Section: Rock Formations and Morphology Of The Valley Of The Kingsmentioning
confidence: 94%
See 3 more Smart Citations
“…The KV is surrounded by steep cliffs of up to 30 m in height (Figure 2b) and small hills with gentle slopes. Other important features were described by Lukovic et al [14] and include low slope angles from the crest of cliffs to the upper plateau, overhanging blocks in cliff walls, gullies crossing the valley, and branching channels used as tourist paths dipping towards the north (<10 • ). Lukovic et al [14] also reported bedding angles from subhorizontal (15 • ) for unfaulted sections to steep angles (30 • ) for those affected by listric faults.…”
Section: Rock Formations and Morphology Of The Valley Of The Kingsmentioning
confidence: 94%
“…Other important features were described by Lukovic et al [14] and include low slope angles from the crest of cliffs to the upper plateau, overhanging blocks in cliff walls, gullies crossing the valley, and branching channels used as tourist paths dipping towards the north (<10 • ). Lukovic et al [14] also reported bedding angles from subhorizontal (15 • ) for unfaulted sections to steep angles (30 • ) for those affected by listric faults. The current morphology is a result of the tectonic fracture network, allowing for rock falls and slides, as well as repetitive fluvial erosion, cycles of flooding, and colluvium accumulation.…”
Section: Rock Formations and Morphology Of The Valley Of The Kingsmentioning
confidence: 94%
See 2 more Smart Citations
“…It is worth mentioning that Rockyfor3D integrates the simulation of the blocking effect of trees on falling rocks, considering the protective effect of forests on falling rocks. Thus, the mitigating effect of forests on rockfalls can be evaluated by comparing the simulation results of the impact range of rockfalls on slopes with and without forests [45]. The Rockyfor3D model utilizes the GIS data format for model input, output, and visualization and allows the use of digital elevation models to represent the terrain and raster maps to represent the input parameters [46].…”
Section: Rockfall Simulations-rockyfor3dmentioning
confidence: 99%